Strengthening the independence criteria: a comparison of the United Kingdom, Malaysia, Hong Kong and Singapore - Mohd. Sulaiman, Aiman @ Nariman (Sweet & Maxwell, 2010)
Since the Asian economic crisis, most Asian countries have carried out reform of their law and regulatory frameworks to address their shortcomings and to prevent a repeat of the economic crisis that some attributed to corporate governance failure. Malaysia, Singapore and Hong Kong have recently revised their applicable corporate governance codes or principles.This discussion provides a comparative study of the differences and similarities in these Codes in relation to: (1) the role of the independent non-executive directors; (2) the independence criteria; and (3) disclosure and verification of the independence criteria. This can be used to provide benchmarking of the applicable rules to counter perceptions of a weak institutional framework on corporate governance.